Impact of climate change on health in Karachi, Pakistan - Maryam Salma Babar; Saema Tazyeen; Hiba Khan; Christos Tsagkaris; Mohammad Yasir Essar; Shoaib Ahmad (Elsevier, 2021)
Climate change is a key indicator of a country's durability in terms of environmental care. When climate shifts from the norm, the whole ecological cycle is disrupted. Karachi has suffered from severe precipitation events and heat waves that have caused outbreaks of malaria, dengue fever, and severe gastroenteritis. These health crises have led to a rise in morbidity and mortality rates in the already low-income city of Karachi. The goal of this review is to highlight the implications of climate change on the health of Karachi residents and actions which need to be undertaken for the betterment of future environmental policies.